Six Thinking Hats - Edward De Bono
Used successfully by thousands of business managers, educators, and government leaders around the world, Six Thinking Hats offers a practical and uniquely positive approach to making decisions and exploring new ideas. Your success in business depends on how you think. "The main difficulty of thinking is confusion," writes Edward de Bono, long recognized as the foremost international authority on conceptual thinking and on the teaching of thinking as a skill. "We try to do too much at once. Emotions, information, logic, hope, and creativity all crowd in on us. It is like juggling with too many balls." The solution? De Bono unscrambles the thinking process with his "six thinking hats": WHITE HAT: neutral and objective, concerned with facts and figures RED HAT: the emotional view BLACK HAT: careful and cautious, the "devil's advocate" hat YELLOW HAT: sunny and positive GREEN HAT: associated with fertile growth, creativity, and new ideas BLUE HAT: cool, the color of the sky, above everything else-the organizing hat Through case studies and real-life examples, Dr. de Bono reveals the often surprising ways in which deliberate role playing can make you a better thinker. He offers a powerfully simple tool that you--and your business, whether it's a start-up or a major corporation--can use to create a climate of clearer thinking, improved communication, and greater creativity. His book is an instructive and inspiring text for anyone who makes decisions, in business or in life.